One Country, Two Systems: Evidence on Retirement Patterns in China - John T. Giles; Xiaoyan Lei; Gewei Wang; Yafeng Wang; Yaohui Zhao (Institute of Labor Economics (IZA), 2021)
This paper documents the patterns and correlates of retirement in China using a nationally representative survey, the China Health and Retirement Longitudinal Study (CHARLS). After documenting stark differences in retirement ages between urban and rural residents, the paper shows that China's urban residents retire earlier than workers in many OECD countries and that rural residents continue to work until advanced ages. Differences in access to generous pensions and economic resources explain much of the urban-rural difference in retirement rates. The paper suggests that reducing disincentives created by China's Urban Employee Pension system, improving health status, providing childcare and elder care support may all facilitate longer working lives. Given spouse preferences for joint retirement, creating incentives for women to retire later may facilitate longer working lives for both men and women.
Keywords: J26; O15; O17; O53; 330; retirement; aging; pensions; urban-rural gap; China; CHARLS